The deuce. Season 2 [videorecording (DVD)]. - Franco, James, 1978-; Gyllenhaal, Maggie, 1977-; Carr, Gary, 1986-; Akinnagbe, Gbenga (Home Box Office, 2019)
A portrayal of the prostitution business in New York in the 1970s. The story follows characters that are forced to venture toward relatively safer and more discreet forms of the same work.